Integrating Behavior Change and Hygiene in Public Policy : Four Key Dimensions - Florez, Rocio (World Bank, Washington, DC, 2014)
During the past decade countries in the Latin American and Caribbean (LAC) region have lifted more than 50 million people out of poverty, yet half of the rural population in the region still lacks access to sanitation and approximately 20 percent to drinking water. In January 2012, policy makers, scholars, and practitioners from nine LAC countries came together in Santo Domingo, Dominican Republic to explore the opportunities and challenges of integrating in a more systematic and sustainable way the promotion of hygiene and sanitation behavioral change into water and sanitation investments. During the conference in Santo Domingo, it became evident that a common understanding is currently emerging from most countries in the sense that infrastructure by itself will not solve the global problems of inadequate access to improved sanitation and potable water, unless people adopt new behaviors. Therefore, there is a need to spread learning on best practices to implement cost effective water, sanitation and hygiene models, which bring about change at home and in the community at scale. This paper highlights key issues that arose in presentations and group discussions during the conference, which, can lead to substantial improvements in the provision of a multi-sector approach to hindering sustainable water and sanitation services for all.